CaCO3-coated indoxacarb deep eutectic solvent complexed with diatomaceous earth improves insecticidal activity against the red imported fire ants - Jiantao Fu; Junfang Wang; Zewen Ma; Di Yuan; Yunfei Zhang; Lanying Wang; Yanping Luo (Ecotoxicology and Environmental Safety)
The red imported fire ants (RIFAs) are a globally important invasive pest that severely affects the ecosystem and human health, and its current control is primarily through chemical pesticides. However, the extensive use of chemical pesticides causes environmental problems, and alternative strategies for controlling this pest are being explored. In our study, we aimed to design a deep eutectic solvent (DES)–CaCO3 system in which RIFAs were used as target insects to increase the lethal activity and behavioural regulation effects on RIFAs via contact and feeding. Indoxacarb (IDC) was made into DESs with three fatty acids, oleic acid (OA), linoleic acid (LA), and linolenic acid (LNA), which showed a significant increase in lethal activity against worker ants compared with IDC. OA@IDC@CaCO3, LA@IDC@CaCO3, and LNA@IDC@CaCO3 nanoparticles were prepared via interfacial precipitation. Characterization of the structures of the three pesticide-carrying nanoparticles revealed that all three fatty acid eutectic solvents formed spherical CaCO3 nanoparticles, with average particle sizes between 0.59 and 0.90 μm, which increased with increasing degree of fatty acid unsaturation. The pesticide loading ranged from 2.13 %⁓3.43 %, and the surfaces were all positively charged and well dispersed. OA@IDC@CaCO3 was relatively more effective and was able to dramatically inhibit the abandonment and foraging behaviours of RIFAs, prolong the time required for these behaviours, and decrease the number of feeding worker ants and the amount of food consumed. OA@IDC@CaCO3 was subsequently compounded with diatomaceous earth (DA), and spiked into baits, which significantly increased the contact and feeding activity of worker ants, inhibited the feeding, digging, and corpse-discarding behaviours of RIFAs. In the field trial, the combined control effect of the DA + OA@IDC@CaCO3 group was 83.38 %, which was greater than the 69.65 % of the commercial agent control group. In this study, IDC bait was co-prepared by using acid as a comelting solvent, CaCO3 as a coating, and DA as a pesticide adjuvant, which improved the activity against RIFAs, prolonged the holding period of IDC, and improved the prevention and control of RIFAs. Therefore, our research provides a simple and feasible approach for designing and constructing novel nanopesticides for RIFAs control.